The Human Gut Microbiome – A Potential Controller of Wellness and Disease - Kho, Zhi Y.; Lal, Sunil K. (Frontiers in Microbiology, 2018)
Trillions of microorganisms co-evolve and dwell symbiotically with the human host, primarily inhabiting our gastrointestinal tract. These gastrointestinal microbes play remarkable roles in human wellness and disease. In this review, the interactions between gut microbiota and the host have been focused on, to provide an overview of the role of gut microbiota in host physiological functions such as metabolism, immunity and protection against pathogens. We elaborate on how the gut microbial imbalance (dysbiosis) may lead to pathogenesis and progression of diseases such as Clostridium difficile infection, inflammatory bowel disease, autism spectrum disorder and obesity. Recent advances in novel therapies derived from microbiome studies to target associated diseases have been reviewed. Despite the ongoing debate on whether gut microbiome plays a role in the above-mentioned diseases, we have in this review gathered evidence showing a clear link between gut microbial dysbiosis and most of these diseases. Underlying mechanisms to many of these microbiome imbalances thus leading to disease, remain to be elucidated. Future microbiome research using the human model need to be undertaken, along with application of standardized experimental protocols to reduce the huge variations in findings across currently available overlapping studies is highly recommended.